2020
DOI: 10.12968/jowc.2020.29.sup9.s29
|View full text |Cite
|
Sign up to set email alerts
|

A dual compression system: preliminary clinical insights from the US

Abstract: There is growing evidence on an interconnection between the venous and lymphatic systems in venous leg ulceration, and the possible effects of prolonged oedema and lymphatic impairment in delayed wound healing. Compression therapy is a widely accepted treatment for venous and lymphatic disorders, as it decreases recurrence rates and prolongs the interval between recurrences. Compression bandages improve venous return, increase the volume and rate of venous flow, reduce oedema and stimulate anti-inflammatory pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
4
0
2
Order By: Relevance
“…The FUSION study evaluated for the first time the performances on healthy volunteers of a new generation of multicomponent compression system, combining two different structures of compressive layers in one unique bandage. The results of this RCT showed that this new system presents a similar profile to the control system, a multicomponent system composed by a shortstretch bandage and a cohesive bandage, widely used in the treatment of venous leg ulcer and oedema of venous origin [21][22][23]25]. Four hours after their application, both systems exerted similar stiffness, with high working pressures and moderate resting pressures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The FUSION study evaluated for the first time the performances on healthy volunteers of a new generation of multicomponent compression system, combining two different structures of compressive layers in one unique bandage. The results of this RCT showed that this new system presents a similar profile to the control system, a multicomponent system composed by a shortstretch bandage and a cohesive bandage, widely used in the treatment of venous leg ulcer and oedema of venous origin [21][22][23]25]. Four hours after their application, both systems exerted similar stiffness, with high working pressures and moderate resting pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Bei dem als Kontrolle verwendeten Kompressionssystem handelte es sich um ein Mehrkomponenten-Kompressionssystem, das eine gepolsterte Kurzzugbinde und eine kohäsive Langzugbinde kombiniert (UrgoK2, Laboratoires Urgo, Frankreich). Dieses System ist in der Behandlung von venösen Beinulzera und Ödemen venösen Ursprungs weit verbreitet (seit 2007 auf dem Markt) und sein Wirksamkeits-und Sicherheitsprofil wurde zuvor durch eine kontrollierte Zufallsuntersuchung (RCT) und mehrere Interventions-und Beobachtungsstudien nachgewiesen [20][21][22][23][24][25][26][27][28].…”
Section: Untersuchte Kompressionssystemeunclassified
See 3 more Smart Citations